Incidencia de las exportaciones no petroleras sobre la degradación ambiental en Ecuador, durante el periodo 1990 – 2021 - Cuenca Castillo, Denisse Sugey (2023)
In Latin America, the emissions of CO2 occupied the 5% of the total in the world, with deforestation 34%, fossil fuels 33% and agriculture with 24%, the main sources of emissions in the region. Meanwhile, the total emissions of carbon dioxide (CO2) in Ecuador come mainly from the agricultural sector with 49.5%. In that sense, the main purpose of this research is to evaluate the relationship between non-oil exports, economic growth, human capital, and the globalization with environmental degradation in Ecuador over the period 1990-2021 through statistics and econometric techniques, with the aim to propose environmental mitigation policies. Thus, the data were gathered from the Ministry of Production, Foreign Trade, Inversions and Fishing (2022), World Bank (2021), Fred Economic Data (2021), Globalization Index (KOF, 2021) and Heritage Foundation (2021). It used techniques such as descriptive and econometric. However, the results were used to verify the presence of a long-term equilibrium relationship between environmental degradation and non-oil exports. Besides, unidirectional causality was demonstrated between the study variables. Consequently, policies should be directed to the State and medium and large companies to realize a fiscal system that will allow them to develop sustainable and inclusive growth for the country, without causing a decline in exports, human capital, and economic growth of Ecuador.